2010
DOI: 10.1097/meg.0b013e32833eb8b0
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal flora imbalance results in altered bacterial translocation and liver function in rats with experimental cirrhosis

Abstract: Gut flora imbalances in cirrhotic rats result in significant changes in BT and liver function in cirrhotic rats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 29 publications
3
34
0
Order By: Relevance
“…Endotoxins concentrations were determined using the chromogenic LAL assay, the most preferred method to quantify endotoxins in biological fluids. Although LAL assay can lead to erroneous endotoxins values due to variations in LAL preparations, cross-reactions, and low detection limits [37], our data is consistent with previous publications [32, 38]. The low number of animals included in our study ( n = 6) may explain the nonsignificant statistical decrease in circulating endotoxins.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Endotoxins concentrations were determined using the chromogenic LAL assay, the most preferred method to quantify endotoxins in biological fluids. Although LAL assay can lead to erroneous endotoxins values due to variations in LAL preparations, cross-reactions, and low detection limits [37], our data is consistent with previous publications [32, 38]. The low number of animals included in our study ( n = 6) may explain the nonsignificant statistical decrease in circulating endotoxins.…”
Section: Discussionsupporting
confidence: 90%
“…Although fecal bacteria do not exactly reproduce the gut microbiota composition [30], they represent a good indicator of the changes arising in the colon [3, 31]. In addition, APA microencapsulated B. infantis ATCC 15697 significantly reduced fecal Gram-negative Enterobacteriaceae and E. coli compared to the saline treatment, in agreement with previous studies [32]. Furthermore, supplementation with the probiotic bacterial formulation nonsignificantly reduced fecal Gram-negative bacteria and increased Gram-positive bacteria.…”
Section: Discussionsupporting
confidence: 83%
“…Amsterdam et al (2010) Patients may be infected in the community and transfer these bacteria to hospitals, as happened for methicillin resistance S. aureus or vice versa (Song et al, 2011). Exchanging of resident flora in the hospital with circulating bacteria in the community, may gradually reduce the efficacy of the prescribed antibiotics in outpatients and render them ineffective (Zhang et al 2010;Moskowitz et al, 2010). Nevertheless, this flow does not reduce the nosocomial resistance rate due to continuous emerging of resistant isolates which may happen under selective pressure of consuming antibiotics in the hospitals (Ozer et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…In rats with carbon tetrachloride-induced cirrhosis, antibiotic therapy and probiotic supplements have decreased systemic endotoxin levels and improved liver tests[265], and in rats with ischemic/re-perfusion liver injury, probiotic supplements with Lactobacillus have reduced the production of pro-inflammatory, pro-fibrotic cytokines and improved liver tests[266] (Table 3). The intestinal microbiota have been implicated in the pathogenesis of PSC[267,268], and a small randomized clinical trial has indicated that treatment with vancomycin or metronidazole can improve serum alkaline phosphatase and bilirubin levels and decrease pruritus[269].…”
Section: Developing Treatment Strategies To Investigatementioning
confidence: 99%